Cardiovascular State of Newly Discovered Diabetic Women. Issue 5699 (28th March 1970) - Weaver, J. A.; Bhatia, S. K.; Boyle, D.; Hadden, D. R.; Montgomery, D. A. D.
Abstract : A cardiovascular study of a group of 90 newly diagnosed diabetic women aged 35 to 75 years was begun in 1965 and a repeat examination was carried out on the same patients in 1968. A high prevalence of ischaemic heart disease was found in these patients at the time of diagnosis, and this finding had some predictive value as regards prognosis over the three-year period. A comparative study with general medical outpatients and long-established diabetics (greater than 10 years' duration of disease) confirmed the high prevalence of ischaemic heart disease in late-onset mild diabetics controlled by diet or oral drugs. It is suggested that this type of milder diabetic patient contributes in undue proportion to the high prevalence of ischaemic heart disease in diabetes.